The Effect of Entrepreneurship Education on Social Entrepreneurship Intentions, Mediating the Need for Achievement, On Mosque Youth in the City of Bandung - Afrianti, Nur Lailah; Kurjono, Kurjono (Perhimpunan Intelektual Muslim Indonesia, 2024)
The purpose of this paper is to examine students' entrepreneurial intentions in the Muslim community in the city of Bandung from the aspect of Islamic values mediated by entrepreneurial attitudes. The Grand Theory used was Ajzen's Theory of Planned Behavior. A total of 220 students from the Muslim community in Bandung City collected data using a questionnaire, a five-point numerical scale. Meanwhile, data analysis using Regression Analysis results identified that Islamic values had a positive and significant effect on social entrepreneurship intentions, while entrepreneurial attitudes mediated the influence of these two variables. The limitations of this study lie in the number of samples and students from the Muslim community in the city of Bandung only. It is suggested to predict the social entrepreneurship intention of Islamic boarding school students in the larger community in the city of Bandung and examine variables other than Islamic values and other SDG components. This study strongly suggests the need to include aspects of creativity in learning in Islamic boarding schools.